Wickerhamomyces spegazzinii sp. nov., an ascomycetous yeast isolated from the fungus garden of Acromyrmex lundii nest (Hymenoptera: Formicidae) - Masiulionis, Virginia E. [UNESP]; Pagnocca, Fernando C. [UNESP] (Microbiology Society, 2016)
A novel ascomycetous yeast species in the genus Wickerhamomyces was isolated from the fungus garden of an attine ant nest, Acromyrmex lundii (Hymenoptera: Formicidae), from Santa Fe province, Argentina. Pairwise sequence alignment of D1/D2 sequences in the GenBank (http://www.ncbi.nlm.nih.gov) database revealed that the novel species is related most closely to Wickerhamomyces subpelliculosus, Wickerhamomyces linferdii, Wickerhamomyces anomalus, Wickerhamomyces siamensis and Wickerhamomyces ciferrii with 96% similarity to the first four. The species name Wickerhamomyces spegazzinii sp. nov. is proposed to accommodate this novel strain, which differs from the above species in melibiose, 5-keto-D-gluconate, succinate, and DL-lactate assimilation among others. The type strain is JLU025T (=CBS 12756T=CBMAI 1619T).
Keywords: Acromyrmex; Ascomycota; Attini; Leaf cutter ant; Wickerhamomyces